Cross-talk mechanisms between adenosine and cannabinoid receptors : implications for the effects of 9-tetrahydrocannabinol on spatial memory - Sousa, Vasco Manuel Cabral, 1981- (2011)
Tese de doutoramento, Ciências Biomédicas (Neurociências), Universidade de Lisboa, Faculdade de Medicina, 2011